Leaching of insecticides used in blueberry production and their toxicity to red worm - Hulbert, Daniel; Raja Jamil, Raja Zalinda; Isaacs, Rufus; Vandervoort, Christine; Erhardt, Susan; Wise, John (Elsevier, 2020)
Soil columns were collected from a blueberry field, and insecticide solutions were allowed to leach through these columns. Insecticides from four different chemical classes were applied at two different rates: the concentration at which the insecticides wash off blueberries under rainfall conditions and the labeled field rate at which they are sprayed. The soil columns were divided into thirds; top, middle and bottom. Soil bioassays using Eisenia foetida Savigny, as an indicator species, were set up to determine the toxicity of the insecticides at a top, middle and bottom layer of the soil column. The mass of E. foetida was also measured after the bioassay experiment was completed. The concentrations at which insecticides wash-off of blueberries from rainfall were not lethal to E. foetida. In order to support mortality data, insecticide residues were quantified in the soil layers for each insecticide. Under field rate leaching conditions, carbaryl showed the high levels of toxicity in the top and middle layers of soil suggesting that it has the highest risk to organisms from leaching. This study will help blueberry growers make informed decisions about insecticide use, which can help minimize contamination of the environment. © 2019 Elsevier Ltd